Pengaruh Motivasi dan Kepuasan Kerja Terhadap Kinerja Perawat Rumah Sakit Putera Bahagia Cirebon - Niken Novitasari (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Nurse's performance is crucial for the hospital, because it can improve services in hospitals where the quality of service of hospital largely determined by human resources in it. The nurse is most employees who are in the hospital, the nurse's performance for that very need to be improved for the Betterment of hospital services. This research aims to look at the picture of the performance of Hospital nurses Son Happy Cirebon and knowing how to influence motivation and job satisfaction on performance of nurses.  The method used in this research is quantitative research method that is descriptive. Analysis method used is by doing the test validity and reliability as well as a test of normality for comparison as well as multiple correlation and regression tests with multiple regression analysis method and processed with SPSS software 25. The results of this study showed that motivation and satisfaction have a correlation with the performance of the nurses, but after a test done together then obtained that motivation has no significant relationship with the performance, but job satisfaction have a significant influence on performance although only amounted to 19.6%. From this it can be concluded that the "motivation and job satisfaction have a correlation with the performance but after tested together just satisfaction of work that has significant relationship with the performance. Then the hospital should focus to improve the job satisfaction of nurses as well as looking for other variables that affect the performance of the nurses.